2020
DOI: 10.1002/cam4.3624
|View full text |Cite
|
Sign up to set email alerts
|

Sequential CD19 and BCMA‐specific CAR T‐cell treatment elicits sustained remission of relapsed and/or refractory myeloma

Abstract: The low rate of durable response against relapsed and/or refractory multiple myeloma (RRMM) in recent studies indicates that chimeric antigen receptor T‐cell (CART) treatment is yet to be optimized. This study aims to investigate the safety and efficacy of sequential infusion of CD19‐CART and B‐cell maturation antigen (BCMA)‐CARTs for RRMM with a similar 3 + 3 dose escalation combined with a toxicity sentinel design. We enrolled 10 patients, among whom 7 received autologous infusion and 3 received allogeneic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Similarly, ex vivo treatment of MM cells with a mixture of both CD19 CAR T cells and BCMA CAR T cells was more effective in reducing colony formation capability than either CD19 CAR T cells or BCMA CAR T cells alone (38,46). Several clinical studies in patients with RRMM have demonstrated a high response rate with the combination of CD19-and BCMA-targeting CAR T cells (47)(48)(49). On-target/off-tumor toxicity consisted of B-cell aplasia and hypogammaglobulinemia (47).…”
Section: Tumor-related Resistance Mechanisms (Soluble) Bcmamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ex vivo treatment of MM cells with a mixture of both CD19 CAR T cells and BCMA CAR T cells was more effective in reducing colony formation capability than either CD19 CAR T cells or BCMA CAR T cells alone (38,46). Several clinical studies in patients with RRMM have demonstrated a high response rate with the combination of CD19-and BCMA-targeting CAR T cells (47)(48)(49). On-target/off-tumor toxicity consisted of B-cell aplasia and hypogammaglobulinemia (47).…”
Section: Tumor-related Resistance Mechanisms (Soluble) Bcmamentioning
confidence: 99%
“…For example, CD38-specific CAR T cells or BCMA/CD38 dual-targeted CAR T cells have the ability to eliminate CD38 + immune suppressor cells, such as regulatory B cells (Breg), in patients with MM (50,132). Bregs were also eradicated by CD19-specific CAR T cells (49). Furthermore, in the face of Treg-mediated inhibition, superior functionality of CD28 over 4-1BB signaling was reported, which is possibly explained through enhanced secretion of proinflammatory cytokines in the presence of Tregs by CD28-based CAR T cells (123).…”
Section: Immune Resistance Conferred By the Tumor Microenvironmentmentioning
confidence: 99%
“…The combination of a CAR-T against BCMA with another CAR-T against CD19 has already been explored in early clinical trials. 70 The development of bi-specific CAR-Ts may be even more effective to prevent disease progression associated to loss of BCMA expression. Bicistronic vectors encoding two CARs avoid the challenge of parallel manufacturing separate CAR-T-cell products, while providing superior efficacy.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Finally, the desire of some patients to reduce their pill burden, prompting them to take their medication only when symptoms appear, should be taken into account when aiming to improve treatment adherence. In this respect, NEPA is the only fixed combination of an NK 1 RA and a 5-HT3RA and has the simplest administration schedule [ 41 ], offering a highly convenient method of administration for most patients. Simple administration schedules would not only facilitate adherence by physicians, but could also prevent patients from making medication errors, a recurring problem during home administration in the delayed phase.…”
Section: Discussionmentioning
confidence: 99%